Непрерывность по параметру решений одномерных линейных краевых задач - Кодлюк, Т.И.; Михайлец, В.А. (Доповіді НАН України, 2010)
Знайдено достатні умови неперервності за параметром розв'язків найбільш загальних лінійних крайових задач для систем лінійних звичайних диференціальних рівнянь першого порядку за більш сильною, ніж рівномірна, нормою соболєвського простору (W1^1)^m. Це дозволило отримати умови неперервності за параметром розв'язків лінійних крайових задач довільного порядку m≥2 за нормою простору W1^m. Sufficient conditions are found for the continuous dependence on a parameter of the solutions of the most general linear boundary-value problems for systems of first-order linear differential equations in the Sobolev space (W1^1)^m, whose norm is stronger than the uniform one. This allows us to obtain sufficient conditions for the continuous dependence on the parameter of the solutions of linear boundary-value problems of an arbitrary order m≥2 in the W1^m-norm.